Analisis Keberadaan Kampus Dalam Meningkatkan Pertumbuhan UMKM Dan Hasil Penjualan Pada UMKM Sekitar Kampus UBP Karawang - Istighna Al Muna; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the existence of a campus on the growth performance of micro, small and medium enterprises on sales results around the campus. The research method used is a qualitative descriptive analysis research. The technique used in this sampling is random sampling, research data collection is carried out by means of the results of interviews and observation techniques on MSME business actors. The number of respondents was 20 MSME business actors. The results of this study indicate that the existence of UBP has prospects in developing a business, increasing business turnover, and generating interest in entrepreneurship around campus. Where there are many types of businesses that can be opened to develop MSME businesses. Business actors only need the latest innovations to make UBP students interested in coming to good places of business. Keywords: Existence of Buana Perjuangan University Campus, Economic growth, UMKM